Assess the effectiveness of structured teaching program regarding Human Milk Banking in terms of knowledge among BSc nursing students - Ms. Tanisha Malik; Ms. Akansha; Ms. Ishika Yadav; Mr. Ablin Soji; Mr. Alex; Ms. Komal (The Bioscan, 2025)
Background: Breastfeeding is the most effective way to feed infants since it is particularly tailored to the infant's needs. In Vienna, Austria, the first human milk bank was created in 1909. In 1989, Lokmanya Tilak Municipal Hospital established Asia's inaugural human milk bank. The "National guidelines on Lactation Management Centres in Public Health facilities" which were published in 2017, include guidelines for setting up Comprehensive Lactation Management Centres (CLMCs) for the purpose of collecting, storing, processing, and dispensing donor human milk for infants admitted to public health facilities as well as offering lactation support to mothers at all delivery points. Nursing students play a crucial role in addressing the complex needs of individuals with structured teaching program on human milk banking. Methodology: A quasi- experimental one group pretest posttest design was employed for the sample was selected using a convenience sampling technique. The intervention consisted of structured teaching program on human milk banking. The analysis of the data was conducted using both descriptive and inferential statistics with SPSS version 20. Result: The study included 80 BSc Nursing students. Pre-intervention knowledge scores ranged from 3 to 19, with a mean score of 11.5 ± 3.2. Following the structured teaching program, post-test scores ranged from 9 to 20, with a significantly higher mean of 16.7 ± 2.4. The mean difference of -5.1 was statistically significant (t = -11, p < 0.01), indicating substantial improvement in knowledge. Among demographic variables, only religion showed a statistically significant association with pre-test knowledge levels (p = 0.01); other variables such as age, gender, and prior exposure to human milk banking showed no significant influence. Conclusion: Structured teaching program was effective in enhancing the competency knowledge on human milk banking of nursing students. As the study findings showed that the mean posttest scores of nursing students were higher rather than pre test. Recommendations: A similar study can be conducted with large sample size in different settings should be conducted to determine the effect of structured teaching program on human milk banking on students competency.